The effect of temperature and relative humidity on the airbone concentration of Pyricularia oryzae spores and the development of rice blast in southern Spain - Castejon Muñoz, M.
(Es, En)
Ilus., 30 ref.
Keywords: ORYZA SATIVA; ENFERMEDADES FUNGOSAS; HONGOS; EPIDEMIOLOGIA; PYRICULARIA ORYZAE; TEMPERATURA; HUMEDAD RELATIVA; ESPAÑA